Clinical and molecular predictors of mortality in patients with carbapenem-resistant Acinetobacter baumannii bacteremia: A retrospective cohort study - Jin Woong Suh; Seung Min Park; Yong Kuk Ju; Kyung Sook Yang; Jeong Yeon Kim; Sun Bean Kim; Jang Wook Sohn; Young Kyung Yoon (Journal of Microbiology, Immunology and Infection, 2024)
Background/Purpose: To investigate the virulence profiles and identify clinical and microbiological predictors of mortality in patients with carbapenem-resistant Acinetobacter baumannii (A. baumannii) bacteremia. Methods: This retrospective cohort study enrolled adult patients with carbapenem-resistant A. baumannii (CRAB). Multivariate logistic regression was used to identify the predictors of 30-day mortality. All isolates were subjected to real-time polymerase chain reaction for virulence factors and genotyped using multilocus sequence typing. Results: Among the 153 patients with CRAB bacteremia, 66 % received appropriate definitive antibiotic therapy. The in-hospital and 30-day mortality rates were 58.3 and 23.5 %, respectively. Ultimately, we enrolled 125 patients with CRAB bacteremia in the analysis, excluding early mortality cases. All CRAB isolates carried blaOXA-23 and blaOXA-51. The clinical strains belonged to 10 sequence types (STs), and the major genotypes were ST191, ST195, ST451, and ST784. The distribution of virulence factors included surface adhesion (Ata, 84.8 %; ChoP, 7.2 %), biofilm formation (OmpA, 76.8 %), killing of host cells (AbeD, 99.2 %), toxins (LipA, 99.2 %), and conjugation (BfmR, 90.4 %). In multivariate logistic regression analysis, hemodialysis due to acute kidney injury and moderate to severe thrombocytopenia were significant risk factors associated with 30-day mortality. However, microbiological factors were not significant predictors. Conclusions: Clinical factors such as hemodialysis due to acute renal injury and moderate to severe thrombocytopenia have a greater influence on mortality in CRAB bacteremia compared with microbiological factors.